Dwa małżeństwa, jeden rozwód. Umowy matrymonialne na wsi w świetle najstarszych akt notariuszy warciańskich z lat 1808–1810 - Szkutnik, Piotr (Zeszyty Wiejskie, 2016)
Notarial acts mainly consist of records on financial agreements. At the beginning of the nineteenth century they included contracts of which peasants were one party. Matrimonial agreements edited in the very article were, in fact, the landowner’s approval of his serf getting married to a bachelor coming from beyond his lands. At the same time the groom was obliged to stay in the village of his wife-to-be. Such contracts were to guarantee landlords that their serfs would not leave the estate. The third agreement was made as to divide chattel between the quarrelling couple who decided to divorce and end their marriage.